Highlights of recent IFPRI food policy research in Pakistan: Reducing poverty and hunger through food policy research - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
This brochure presents some of the highlights of IFPRI’s research, which has impacted Pakistani policies related to food rations and storage, energy subsidies, water management, poverty reduction, and other areas over the past 30 years.